2016
DOI: 10.1002/ceat.201400745
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of Free Fatty Acids Derived from Waste Cooking Oil with Octanol: Process Optimization and Kinetic Modeling

Abstract: The synthesis of lubricant‐grade ester using waste cooking oil (WCO) as the primary feedstock is characterized in detail and optimized. WCO was initially hydrolyzed using Candida rugosa lipase to convert triglycerides into free fatty acids (FFA). Subsequently, the FFA were esterified with octanol by a heterogeneous catalytic reaction in batch mode. Both the hydrolysis and esterification steps were optimized in terms of relevant process parameters, employing the well‐known response surface methodology. The fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…and the H 2 O:RO (v/v) ratio (from 4:1 to 1:2). In previous studies it was found that the maximum TG conversions were 93% for 1:2 (v/v) ratio after 10 h reaction, 70% for 4:1 (v/v) ratio after 24 h reaction, and 92% for 4.12:1 (v/v) ratio after 30 h reaction (Chowdhury et al, 2016). Based on these results, we assayed H 2 O:RO ratios (v/v) within a similar range (from 4:1 to 1:2), fixing the reaction time to 24 h. To assess the most suitable conditions for the hydrolysis reaction, the acidity index was chosen as the parameter to be followed.…”
Section: Hydrolysis Of Triglyceridesmentioning
confidence: 94%
See 1 more Smart Citation
“…and the H 2 O:RO (v/v) ratio (from 4:1 to 1:2). In previous studies it was found that the maximum TG conversions were 93% for 1:2 (v/v) ratio after 10 h reaction, 70% for 4:1 (v/v) ratio after 24 h reaction, and 92% for 4.12:1 (v/v) ratio after 30 h reaction (Chowdhury et al, 2016). Based on these results, we assayed H 2 O:RO ratios (v/v) within a similar range (from 4:1 to 1:2), fixing the reaction time to 24 h. To assess the most suitable conditions for the hydrolysis reaction, the acidity index was chosen as the parameter to be followed.…”
Section: Hydrolysis Of Triglyceridesmentioning
confidence: 94%
“…The conditions assayed included an enzyme concentration between 0.6 and 1.2 g dm −3 acting at pH 7, 30 °C temperature, 1 atm pressure, water-to-oil molar ratios from 1:2 to 4:1 (v/v) ( Table 2) and 24 h reaction time. These conditions were chosen because they are in the range of more suitable conditions for TG hydrolysis pointed out by other authors (Chowdhury et al, 2016). Subsequently, the samples were centrifuged and the oil phase was separated from the aqueous phase and the acidity index of the oil phase was determined.…”
Section: Hydrolysismentioning
confidence: 99%
“…“Adeq Precision” >4 is desirable . In this model, this ratio is 31.087, which represent an adequate signal . Hence, it can be concluded that the model can be used to navigate the design space.…”
Section: Resultsmentioning
confidence: 85%
“…Therefore, WCO was chosen for a further set of experiments because there are no reports in the literature on the application of this feedstock for the production of biolubricants by enzymatic transesterification. Only the production of biolubricants from WCO by two-step reactions has been reported: hydrolysis of WCO followed by esterification of the free fatty acids [ 1 , 2 , 73 ].…”
Section: Resultsmentioning
confidence: 99%